Agricultural Policy and Economic Growth of Nigeria - Ogundiwin, Ijeoma j.; Asikhia, Olalekan; Binuyo, Adekunle; Amos, Benita (NIU Journal of Social Sciences, 2021)
The objective of every independent nation like Nigeria is to improve the standard of living of its citizenry and promote economic growth. Despite huge sums of money allocated to the agricultural sector over these years, there was little or insignificant improvement in agricultural production because successive governments only used the policies to embezzle public funds to the total neglect of food production by refusing to pay farmers the true value of their crops and at the same time selling fertilizer and seeds to them at high prices . The study adopted ex-post facto research design. Economic data were sourced from Central Bank of Nigeria Statistical Bulletin and World Governance Indicator from 1981-2017. Data were analysed using descriptive statistics and multiple regression analysis. Agriculture policy had positive but non-significant moderating effect on the relationship between agricultural exports and the economic growth of Nigeria (âˆ†R 2 =0.024; Î² = -0.0001; t(185) =4.3743; p<0.05). The study concluded that agricultural policy impacted the economic growth of Nigeria. The study recommended that an effective and committed policy implementation by the government is needed to improve economic growth. Furthermore, the Nigerian government should provide additional funding for the agricultural sector to raise its productivity and increase its contributions to economic growth. Keywords: Agricultural, Economic, Growth, Gross Domestic Product, Policy, Sector.